Understanding the Influence of Aging Time on the Eutectic Growth of Sn-xBi Solder Alloys - S. L. A. Dantas; Bruno Sobral; A. Garcia; J. E. Spinelli; B. L. Silva (Materials Research, 2025)
In order to support new packaging technologies driven by new demands for rapid data communication in 5G and IoT (Internet of Things), as well as prevent issues related to thermal expansion and deformation. Studies aimed at understanding the effect of temperature and time during service life of soldered parts are rare, especially for the Sn/Bi eutectic arrangement. Therefore, this study aims to understand the influence of the aging time (30, 60 and 90 days) at 100 °C on the local eutectic coarsening of Sn-xBi alloys (x=34, 52 and 58 wt.% Bi). Directionally solidified samples, solidified at cooling rates compatible with soldering, were examined using SEM with the aid of Energy-dispersive X-ray spectroscopy analysis, and Vickers hardness tests to assess both untreated and treated eutectic microstructures. The sample having lower Bi content showed higher coarsening sensitivity over time due to increased Bi flow from the β-Sn phase to the eutectic Bi.